ANALISIS WACANA PESAN POLITIK DALAM VIDEO “MA’RUF AMIN-DEDDY CORBUZIER PODCAST” DI YOUTUBE DEDDY CORBUZIER - Rahmad Bakri; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The video "Ma'ruf Amin- Deddy Corbuzier Podcast" contains many things and messages conveyed by Mr. K.H. Ma'ruf Amin regarding the issues that dismissed him, problems that occurred in Indonesia to his personal life. This study aims to find out the analysis of text dimensions, know the analysis of social cognition dimensions, and know the dimensions of the social context of political messages conveyed by K.H. Ma'ruf Amin in the video "Ma'ruf Amin-Deddy Corbuzier Podcast" on Deddy Corbuzier's YouTube. This research uses qualitative descriptive method. Data collection was carried out by means of observation, documentation and study of existing literature with an analysis unit of eight political messages taken in the entire video "Ma'ruf Amin-Deddy Corbuzier Podcast" on Deddy Corbuzier's youtube. The subject and object to be studied are the political messages conveyed in the video "Ma'ruf Amin-Deddy Corbuzier Podcast" on Deddy Corbuzier's youtube. Data analysis techniques using Teun A. Van Dijk's model discourse analysis using three dimensions, namely text, social cognition, and social context. In addition, the technique of checking the validity of the data uses source triangulation. The results showed that from the analysis of the discourse model Teun A. Van Dijk explained, the first in the dimension of the text is spelled out the meaning of a political message studied that discusses various aspects from economics to the field of government. Second, the social cognition of K.H. Ma'ruf Amin who has an Islamic background in providing political messages. Third, the social context that connects so closely the problems that exist in the political message regarding the current state of Indonesian society Keywords: Discourse Analysis, Political Messages, Podcast